Organic geochemical analysis of river samples from Baker River and Baker-Martinez Fjord - Sophie Hage; Sébastien Bertrand; Benjamin Amann; Brian Reid; Elke Vanderkerkhove (PANGAEA, 2025)
This dataset presents bulk organic geochemical data (TOC, d13C) obtained by EA-IRMS analysis on suspended river sediments at the surface of five rivers of Chilean Patagonia (44-48?S). The samples were collected between 2008 and 2019 in all seasons. All the water samples were stored in pre-rinsed I-chem cubitainers and filtered within 48 hours using a pressurized filtration system equipped with a 90 mm diameter PES membrane (pore size 0.22 μm)